Pola Perilaku Prososial Mahasiswa Relawan Solo Mengajar - Denni Rahmawati, Anggerhana; , Dra. Zahrotul Uyun, M.Si (2016)
Abstract This research is proposed to describe and understand the prosocial behavior pattern of Solo Mengajar volunteer students. Criteria of subjects in this research are those who become volunteer of Solo Mengajar at seven Taman Cerdas and two Rumah Mengajar who are still student in university. Research method used is qualitative method by using open questionnaire to acquire data from subjects. Result of this research indicates that there are several volunteer students have not high pro-social behavior seen by the way they help the students of Solo Mengajar only in a crucial time and situation, such as when riots and quarrels; Subject feeling sad and disappointed if the help given was not favorable to him; Subject does not have any friends in Solo Mengajar, Subject doesn't feel happy to blunt to other people; Subject doesn't want to share anything to other people, and; Subject chooses to prioritize people's rights. Factor that makes many of the subjects decide to help others by being a volunteer is the fact that people who is being helped need help more than the helper do. Whereas the disruptive factor in giving help to others is time as the volunteers still need to study and do home works from their campus. Keywords: pro-social behavior, volunteer student, Solo Mengajar